Greek Researches on St. Athanasius the Great in the 20th Century - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
Ioannis Kaminis, Greek Researches on St. Athanasius the Great in the 20th Century. The purpose of the current paper is to identify and present the studies about Athanasius of Alexandria in Greek language during 20th century. Athanasius of Alexandria is one of the most important figures in Christianity, because of his contribution to the elucidation and the development of Christian theology. The studies about Athanasius of Alexandria can be divided in two periods. The first period lasts until 1937 and is comprised by studies which are more focused in the historical value of Athanasius who is considered also as a great combatant of heresies. The second period starts in 1937 with the erudite study of Michael Konstantinides, Athana-sius the Great and his Epoch. Moreover, this study is a landmark because in inaugurates a new era of interest for the great Father of the Church. By the end of the 2nd World War new studies are brought are presented which explore different aspects of the life and the work of Athanasius of Alexandria. Furthermore during the 1960s and because of the theological ferment in Greece during that time the interest about Athanasius grows even more. Keywords: Athanasius of Alexandria, Greek Fathers, Modern Greek Theology, Systematic Theology